Generalized Cubic Aggregation Operators with Application in Decision Making Problem - Muhammad Shakeel; Saleem Abdullah; Aliya Fahmi (Journal of New Theory, 2018)
There are many aggregation operators and their applications have been developed up to date, but in this paper we introduced the idea of generalized aggregation operator. The main idea of this paper is to study the generalized aggregation operators with cubic numbers. In this paper, we introduced three types of cubic aggregation operators called generalized cubic weighted averaging (GCWA) operator, generalized cubic ordered weighted averaging (GCOWA) operator and generalized cubic hybrid averaging (GCHA) operator. We extend the theory of cubic numbers to generalized ordered weighted averaging operators that are characterized by interval membership and exact membership. In last section we provide an application of these aggregation operators to multiple attribute group decision making problem.